PENGARUH KUALITAS KOMPOS PAITAN (Tithonia diversifolia) DAN KOTORAN SAPI TERHADAP HASIL DAN BINTIL AKAR TANAMAN KEDELAI (Glycine max. L.) PADA ALFISOL - Lelalovita Siregar; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Indonesia has around 82% of the total 58 million ha of agricultural land, which is classified as sub-optimal due to intensive land management and not concerned with soil fertility. Therefore, it is necessary to add organic material which is expected to increase soil fertility. Compost is an organic soil repairer that can reduce the use of chemical fertilizers so that it can increase yield and plant root nodules are largely determined by the quality parameters contained therein. This study was aimed to explore the effect of quality of paitan (Tithonia diversifolia) compost and cow dung on soybean (Glycine max. L.) yield and root nodules. This study was conducted using a randomized block design with two stages, i.e., compost making with five treatments and three replications and compost application with six treatments and three replications. The results showed that the quality of the compost was able to increase the yield and nodules of soybean n plants. There was a positive correlation between compost quality and soybean yield.